(untitled) (Bangladesh Journal of Botany, 2011)
Osbeckia truncata D. Don ex Wight & Arn., (Melastomaceae) rediscovered after more than one hundred years from Fashiakhali wildlife sanctuary of Chakaria Upazila of Cox’s Bazar district, Bangladesh. Key words: Osbeckia truncata; Melastomaceae; Rediscovery; Bangladesh DOI: http://dx.doi.org/10.3329/bjb.v40i1.8005 Bangladesh J. Bot. 40(1): 101-103, 2011 (June)